High-entropy lead-free perovskite for high-performance ferroelectric applications - Mishra, Rajesh Kumar (Universidade Estadual Paulista (Unesp), 2024)
In order to execute the proposal’s objective, we have synthesized many novel multicomponent high entropy oxides and studied their structural, microstructural and functional properties in details. In the first study, we have synthesized a novel (Al0.2Co0.2Fe0.2Ni0.2Ti0.2)3O4 high entropy oxide (HEO) through modified solid state method (ball milling + sintering) and investigated the structural, microstructural, dielectric, electric, and magnetic properties comprehensively. The study reports the cumulative study of dielectric, electric, and magnetic properties of the spinel HEO for the first time in detail. The obtained HEO has a single-phase cubic spinel structure with Fd-3m space group, confirmed through X-ray diffraction and Raman spectroscopy techniques. Moreover, Raman spectroscopic analysis also confirms that the synthesized spinel HEO has phase homogeneity and possesses an inverse spinel. The dielectric and magnetic characterizations reveal a better dielectric permittivity of ε'=35 at 1 MHz and high saturation magnetization Ms = 8.58 emu/g with low magnetic coercivity. The leakage current characteristics studied in terms of J-E curves indicate an ohmic conduction mechanism at a low electric field. Moreover, the high dielectric permittivity with resistive switching behavior (observed in the J-E curve) indicates its potential application in resistive switching memory devices, which have better functionality and enhanced scalability. (This work has been published in Journal of Physics and Chemistry of Solids, August 2024). In the second study, we have investigated the effect of sintering temperature on structural, microstructural, and electrical behavior of (CoAlFeNTi)3O4 high entropy oxide (HEO). The HEO is synthesized through the modified solid-state reaction method at two different sintering temperatures (1100 oC and 1250 oC) and characterized further with the XRD, Raman, and SEM for structural and microstructural behavior. XRD analysis confirmed the formation of a single cubic spinel phase with the Fd-3m space group. In addition, Raman analysis also confirmed that the synthesized HEOs have a spinel structure with an inverse spinel nature. With the enhancement of the sintering temperature, XRD analysis indicates that the crystallinity and crystallite size of the HEO enhanced. The current density (J) versus applied electric field (E) characteristics displayed that both 1100 oC and 1250 oC sintered HEOs possessed leakage current density at zero applied electric field and an ohmic conductance of 4.59×〖10〗^(-10) mhos/cm and 3.43×〖10〗^(-10) mhos/cm respectively. Moreover, J - E characteristics also showed that the enhancement of sintering temperature enhanced the resistive switching behavior of the different temperature sintered spinel HEOs. This improved resistive switching behavior in the J-E curve indicates that the synthesized spinel HEO can find potential application in resistive switching memory devices. (The revision of the manuscript has been submitted in the Journal Electroceramics, August 2024). In spite of these two published/submitted works, a few other studies have also been carried out (but not communicated/submitted to the Journal), details of which are given in the ‘List of works prepared’ section.
High-entropy lead-free perovskite for high-performance ferroelectric applications
https://doi.org/10.1016/j.jpcs.2024.112249 https://doi.org/10.1007/s10832-024-00370-0
Keywords: High entropy ceramics; Functional properties